PENGARUH KUALITAS PELAYANAN DOKTER AHLI TERHADAP KEPUASAN PASIEN DI RSUD SIWA KECAMATAN PITUMPANUA KABUPATEN WAJO (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
The purpose of this study was to describe and explain the effect of the quality of expert doctor's services on patient satisfaction in Siwa Hospital, Pitumpanua District, Wajo Regency. This study used quantitative research methods with data collection techniques using questionnaires strengthened by the results of field observations and documentation studies. The results of this study showed that the results of the regression (influence) of the variable (X) on the variable (Y) simultaneously was only .324 or 32.4%, which meant that the effect of the quality of expert doctor services on patient satisfaction in Siwa Hospital, Pitumpanua District, Wajo Regency was not significant. . While the influence of the variable quality of expert doctor's service (X) on the patient satisfaction variable (Y) partially showed the  results found that no more than .242 or 24.2% . Also showed the effect of the quality of expert doctor's service on patient satisfaction in Siwa Hospital, Pitumpanua District,  Wajo Regency was classified as insignificant.